Time to shake the world, shall we? - Yow, Chong Lee (2014)
A shocking news reached many of us when a high scoring student from Penang, suspected suicide, is found dead at the compound of his apartment. The boy is said to have gone though miserable months of stress due to his increasingly burdening study. This kind of news has generally made many of us feel down, that it has become a trend recurring every year, particularly near the exam or result announcing months